Legal Protection of Registered Marks Case Study: Ruling Number 1850 K/Pdt.Sus-HKI/2022 - Fahmi Fairuzzaman; Kelvin Dean Putra Mahardhika (Proceeding International Conference Restructuring and Transforming Law, 2023)
Trademarks are a clear part of intellectual property that plays a vital role in the economic cycle of an industry in the field of trading goods and services. One of them is that the brand becomes an image of product quality and helps attract consumer interest in new products. Brand issues are still a problem that continues to be on the court table, therefore there must be strict regulations governing this matter. apply normative juridical research methods by examining library materials, namely primary and secondary legal materials. After the legal materials are collected, analysis is carried out and appropriate conclusions are drawn regarding the problems contained in the problem formulation. This research applies data analysis techniques using deductive logic. This conclusion is based on an analysis of the regulations regarding trademarks and decision Number 1850 K/Pdt.Sus-HKI/2022. This brand dispute will be analyzed according to existing regulations, from a brand law perspective in order to understand its essence and intent in resolving the legal problems discussed in this research. Therefore, here the panel of judges is required to be fair in giving a fair decision. So that no party feels cheated and seeks legal protection in other courts. And the theory of legal protection means that when a judge examines a case in this chapter, a trademark case must look at various existing legal literature and interpret it clearly in line with the applicable arguments.